KUALITAS SEMEN BEKU SAPI BALI DENGAN PENAMBAHAN BERBAGAI DOSIS VITAMIN C PADA BAHAN PENGENCER SKIM KUNING TELUR - Faradina Kusuma Savitri; Sri Suharyati; Siswanto . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
The aim of this research was to know what the effect of C vitamin increament (ascorbat acid)in skim egg yolk extender to semen motility and life percentage of sperm cell. This research wasconducted in Regional Technical Service Unit-Regional Artificial Insemination Office Lampung,Terbanggi Besar District on 18 th –25 th April 2014. The treatment of this research are P1 (without Cvitamin increament), P2 (1,50 mM C vitamin increament), P3 (2,50 mM C vitamin increament), P4(3,50 mM C vitamin increament), P5 (4,50 mM C vitamin increament) in skim egg yolk extender andevery treatment repetitions for three times. The data obtained was analyzed by using variance analysis5%. Results of this research showed that increament C vitamin dosage into skim egg yolk extenderwas no significantly (P>0.05) to sperm motility and life percentage of sperm.